Analisis Cerpen Ahmad Tohari dalam Judul “Rumah yang Terang - Dani Maulana; Fajar Muhammad Fadlillah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
One of Ahmad Tohari's short stories is The Bright House, in the collection of short stories Smile Karyamin (2013). The short story records the incident of electricity entering a village. As narrated in the short story, the existence of electricity has a significant impact on society, both positively and negatively. The positive side brings physical changes with the presence of lights and other facilities to support people's lives. On the other hand, this positive aspect has a negative impact, namely the "death" of culture and human aspects with the presence of technology which has an impact on changing perspectives and making them a market for advanced capitalism with the existence of technology and information. The formulation of the problem in this paper concerns the problems that exist in society related to the existence of technology and information after the presence of electricity which allows people to experience dependency and changes in mindset due to interaction with the outside world. This writing method is by showing forms of inhumanism in the short story. The theory used is the theory of postmodernism by Jean Francois Lyotard as explained by Struart Sim regarding the Inhuman condition. The result of this discussion is Inhumanism in rural communities caused by the presence of electricity as the initial foundation for the presence of technology in the form of the loss of cultural habits for the local community, both in terms of habits of responding to nature or new conflicts after the presence of electricity in society. This happens because of the presence of artificial life, replacing the role of nature which has been a part of people's lives like the existence of the moon. Access to information is obtained by the community after getting to know technology which presents new values and is different from the values they previously had as a communal society